Comparison Between Early and Late Tracheostomy in ICU Patients - Fatima, Wajeeha; Awan, Aamer Ayub; Afzal, Amna; Waseem Yaseen, Hafiz Muhammad; Abdul Haseeb,; Saleem, Satwat; Zahoor, Muhammad Mohsin; Shuaib, Hamza (Indus Journal of Bioscience Research, 2025)
Tracheostomy remains a pivotal procedure in the management of critically ill patients requiring prolonged mechanical ventilation. This descriptive case series aimed to compare the clinical outcomes of early (<10 days) versus late (>10 days) tracheostomy among ICU patients at Lahore General Hospital over a six-month period. A total of 96 patients were included, with 54 undergoing early tracheostomy and 42 receiving late tracheostomy. Outcomes assessed included duration of mechanical ventilation, ICU and hospital stay, incidence of ventilator-associated pneumonia (VAP), subglottic stenosis, and mortality. Patients in the early tracheostomy group experienced significantly reduced durations of mechanical ventilation (7.3 ± 2.1 vs. 11.5 ± 3.2 days, p < 0.001), ICU stay (10.2 ± 2.9 vs. 14.7 ± 4.1 days, p < 0.001), and total hospital stay (15.6 ± 3.7 vs. 20.8 ± 4.6 days, p < 0.001). The incidence of VAP was notably lower in the early group (5.6%) compared to the late group (21.4%, p = 0.02). Although subglottic stenosis and mortality did not differ significantly between groups, a lower mortality trend was observed in the early tracheostomy cohort (13% vs. 26.2%, p = 0.09). These findings align with previous evidence suggesting early tracheostomy facilitates earlier weaning, reduces infectious complications, and improves resource utilization. The results advocate for the integration of early tracheostomy into ICU care protocols, while emphasizing individualized patient assessment. Further large-scale studies are needed to substantiate these findings and guide standardized timing recommendations.